Diversity of Phenotype and Genetic Etiology of 23 Cystinuria Saudi Patients: A Retrospective Study - Alghamdi, Malak; Alhasan, Khalid A.; Taha Elawad, Areej; Salim, Suha; Abdelhakim, Marwa; Nashabat, Marwan; Raina, Rupesh; Kari, Jameela; Alfadhel, Majid (Frontiers in Pediatrics, 2020)
Background: Cystinuria is an inborn error of metabolism that manifests with renal stones due to defective renal epithelial cell transport of cystine and dibasic amino acids which resulted from pathogenic variants in the SLC3A1 and/or SLC7A9 genes. Among nephrolithiasis diseases, cystinuria is potentially treatable, and further stone formation may be preventable. We report 23 patients who were identified biochemically and genetically to have cystinuria showing the diversity of the phenotype of cystinuria and expanding the genotype by identifying a broad spectrum of mutations. Patients and Methods: This is a multicenter retrospective chart review, where clinical and biochemical data, genetic analysis, and the progress of the disease were documented over five years at two centers from 2014 until 2019. Results: Of 23 patients who were identified biochemically and/or genetically to have cystinuria, 14 (62%) were male. Thirteen patients were homozygous, and two were heterozygous for the SLC3A1 gene. Seven were homozygous and one was compound heterozygous for the SLC7A9 gene. We have detected twelve genetic variants including five novel variants. SLC3A1 gene variant c.1400 T> A (p.Met467Lys) is found in 38% of our cohort. Although twenty-one patients required surgical intervention, none developed ESRD. The number of stone episodes per year varied widely (median frequency of 0.45 stones/ per year, range between 0.06–78.2), with no significant difference in stone events per year between sexes (P=0.73). Conclusion: Despite the high rate of consanguinity in Saudi Arabia, there was a broad spectrum of genetic variants. Most of our patients are homozygous recessive for SLC genes with multiple generations affected which indicates early screening and prevention of disease in these families. Phenotypic heterogeneity is well documented in our cohort even with the same genotype and the first stone episode age was variable but most commonly seen in the first decade of life.